2019
DOI: 10.2355/isijinternational.isijint-2018-866
|View full text |Cite
|
Sign up to set email alerts
|

Physical Modeling of Asymmetrical Flow in Slab Continuous Casting Mold due to Submerged Entry Nozzle Clogging with the Effect of Electromagnetic Stirring

Abstract: Submerged Entry Nozzle (SEN) clogging is a serious problem for continuous casting process and slab quality. In order to investigate the impact of the SEN clogging rate on the flow field and the optimization effect of electromagnetic stirring (EMS) on the asymmetrical flow due to the SEN clogging, a 1:5 scaled mercury model, with various SEN clogging rates and different electromagnetic stirring currents was established and the flow velocity was measured by means of Ultrasonic Doppler Velocimetry (UDV). S index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 38 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…It can be seen that electromagnetic force increases with the EMS current, as the EMS current increases from 400 to 800 A, the maximum electromagnetic force is 2133 N/m 3 and 7950 N/m 3 . In order to validate the mathematical model, a 1/5th scaled physical model using mercury when EMS is not applied was established; the fluid velocity in the mold was measured by means of ultrasound Doppler velocimetry (UDV), and Li et al [30] as the authors published this apparatus' description in ISIJ International. Meanwhile, a mathematical model was set corresponding to the physical model both on the geometry and material properties, etc.…”
Section: Validation Of Electromagnetic Field and Flow Fieldmentioning
confidence: 99%
“…It can be seen that electromagnetic force increases with the EMS current, as the EMS current increases from 400 to 800 A, the maximum electromagnetic force is 2133 N/m 3 and 7950 N/m 3 . In order to validate the mathematical model, a 1/5th scaled physical model using mercury when EMS is not applied was established; the fluid velocity in the mold was measured by means of ultrasound Doppler velocimetry (UDV), and Li et al [30] as the authors published this apparatus' description in ISIJ International. Meanwhile, a mathematical model was set corresponding to the physical model both on the geometry and material properties, etc.…”
Section: Validation Of Electromagnetic Field and Flow Fieldmentioning
confidence: 99%
“…This means that the distribution of the temperature field with SEN clogging is not uniform, inducing the non-uniform development of the solidified shell. In our previous paper, we introduced the symmetric index S to quantitatively judge whether the horizontal flow pattern is symmetric or not [31]. In this study, we chose the symmetry of the horizontal plane where the electromagnetic force reached its maximum to characterize the symmetry of flow field with SEN clogging.…”
Section: Effect Of Sen Clogging Rate On the Symmetry Of Flow Fieldmentioning
confidence: 99%
“…They show good agreement between the predictions and UDV measurements. More experimental details are given in previous research [29]. The physical experiment system is shown in Figure 2c.…”
Section: Mathematical Model Validationmentioning
confidence: 99%
“…In fact, recent studies have shown that the appropriate use of combined stirring and braking has the potential to optimize the flow of molten steel and to compensate for the limitations of a single electromagnetic field [24,25]. Multifunction electromagnetic driving which combines EMS and EMBr is the development trend of the current control technology of steel flow in a continuous casting mold [26][27][28][29]. However, there are few studies on the steel/slag interface behavior under multifunction electromagnetic driving.…”
Section: Introductionmentioning
confidence: 99%